2010
DOI: 10.1530/eje-10-0583
|View full text |Cite
|
Sign up to set email alerts
|

Changes in coagulation indexes and occurrence of venous thromboembolism in patients with Cushing's syndrome: results from a prospective study before and after surgery

Abstract: Objectives: To evaluate whether patients with Cushing's syndrome (CS) had i) changes in coagulative and fibrinolytic parameters associated with CS activity and ii) higher prevalence of venous thromboembolic events (VTE). Design: Prospective study conducted on patients with CS evaluated at diagnosis and 12 months after surgery. Patients and methods: Forty patients with active CS (36 with Cushing's disease (CD) and 4 with an adrenal adenoma) were evaluated. Forty normal subjects and 70 patients with non-ACTH-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
118
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 31 publications
(34 reference statements)
11
118
3
3
Order By: Relevance
“…The D-dimer levels were found to be elevated [6] or unchanged [32] relative to those in healthy control subjects. No changes in the D-dimer levels in patients with soCS were observed at 28 and 77 days after medical treatment [28].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The D-dimer levels were found to be elevated [6] or unchanged [32] relative to those in healthy control subjects. No changes in the D-dimer levels in patients with soCS were observed at 28 and 77 days after medical treatment [28].…”
Section: Discussionmentioning
confidence: 77%
“…Regarding the mechanistic insight, patients with CS have been reported to present with elevated plasma levels of clotting factors, including VWF and factor VIII, which increases the plasma D-dimer levels [6,28,29]. On the other hand, the levels of PAI-1, the primary inhibitor of the fibrinolytic system, were found to be elevated in patients with CS [6,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypercoagulable state can lead to increased incidence of thromboembolic episodes in the postoperative period or during diagnostic procedures such as inferior petrosal sinus sampling [9][10][11][12][13][14]. Boscaro et al demonstrated significantly higher thromboembolic mortality and morbidity in a group of Cushing's syndrome patients receiving no anti-thromboembolic prevention in comparison with those in a group receiving prophylactic treatment with the use of warfarin or heparin [14].…”
Section: Introductionmentioning
confidence: 99%